The chaetodontidae coral fish in the waters of Poopoh Village, Tombariri District - Ratih, Mutiara; Rondonuwu, Ari; Rangan, Jety; Manginsela, Fransine; Kambey, Alex D.; Sangari, Joudy; Menajang, Febry S. I. (Jurnal Ilmiah PLATAX, 2023)
This study aims to determine the number of species, number of individuals, density, and community structure of the Chaetodontidae. The study was conducted in the waters of Poopoh Village, Tombariri District, Minahasa Regency, North Sulawesi Province, at Poopoh Cape, which is located within the conservation area of Bunaken National Park, South Zone, marine protected zone. Data collection was conducted at depths of 3 and 10 meters. At each depth, 2 transects were placed, each with a length of 25 meters, using the Underwater Visual Census (UVC) method with an observation area of 125 m². The results of the study showed that the Chaetodontidae fish was found, consisting of 4 genera, namely Chaetodon, Forcipiger, Heniochus, and Hemitaurichthys, with 18 species and 598 individuals. A higher number of species was found at 3 meters depth. One of the most frequently encountered species was Hemitaurichthy polylepis, with a density of 0.442 individuals per square meter. Based on the data analysis, the species diversity index (H’) at 3 meters depth was classified as high, while at 10 meters depth, it was classified as low. This result is consistent with the evenness index (J’), which indicates that the 3-meter depth has a more stable community compared to the 10-meter depth. On the other hand, the dominance index (D) shows the opposite trend, with a higher species dominance level at a depth of 10 meters. Keywords: Chaetodontidae, Indicator fish, poopoh village Abstrak Penelitian ini bertujuan untuk menentukan jumlah spesies, jumlah individu, kepadatan, dan struktur komunitas Chaetodontidae. Penelitian ini dilakukan di perairan Desa Poopoh, Kecamatan Tombariri, Kabupaten Minahasa, Provinsi Sulawesi Utara di Tanjung Poopoh, yang terletak di dalam kawasan konservasi Taman Nasional Bunaken, bagian Selatan, zona perlindungan bahari. Pengambilan data dilakukan pada kedalaman 3 dan 10 meter. Pada setiap kedalaman diletakkan 2 transek, masing-masing dengan panjang 25 m dengan menggunakan metode Underwater Visual Census (UVC) dengan luas pengamatan sebesar 125 m2. Hasil penelitian menunjukkan bahwa famili ikan Chaetodontidae yang ditemukan di perairan Desa Poopoh, Kecamatan Tombariri, terdiri dari 4 (empat) genus, yaitu Chaetodon, Forcipiger, Heniochus, dan Hemitaurichthys dengan 18 spesies dan 598 individu. Jumlah spesies yang lebih tinggi ditemukan pada kedalaman 3 m. Salah satu spesies yang paling sering ditemukan adalah Hemitaurichthy polylepis, dengan kepadatan 0,442 individu per meter persegi. Berdasarkan hasil analisis data, indeks keanekaragaman spesies (H’) pada kedalaman 3 m tergolong tinggi, sedangkan pada kedalaman 10 m tergolong rendah. Hasil ini konsisten dengan indeks keseimbangan (J’), yang menunjukkan bahwa kedalaman 3 m memiliki komunitas yang lebih stabil dibandingkan dengan kedalaman 10 m. Di sisi lain, indeks dominansi (D) menunjukkan kecenderungan yang berlawanan, dengan tingkat dominansi spesies yang lebih tinggi pada kedalaman 10 m. Top of Form Kata kunci: Chaetodontidae, ikan indikator, Desa Poopoh